Cardiovascular Considerations for the Internist and Hospitalist in the COVID-19 Era (2020)
It is clear that existing cardiovascular disease is a major risk factor for COVID-19 and related adverse outcomes. In addition to acute respiratory syndrome, a large cohort also develop myocardial or vascular dysfunction, in part from inflammation and renin angiotensin system activation with increased sympathetic outflow, cardiac arrhythmias, ischemia, heart failure, and thromboembolic complications that portend poor outcomes related to COVID-19. We summarize recent information for hospitalists and internists on the front line of this pandemic regarding its cardiovascular impacts and management and the need for cardiovascular consultation.